Movimientos sociales en red, usos de Internet y ciudadanía universal de las migraciones transnacionales: análisis del Foro Social Mundial de las Migraciones - Denise Cogo; Lara Nasi (Les Cahiers ALHIM)
This article presents the results of a study that aimed to analyze the uses of internet made by social movement networks in order to build the agenda of universal citizenship for transnational migrations, in the context of World Social Forum on Migrations (WSFM). Methods included the observation of WSFM website (http://www.wsfm2012.org), as well as websites from organizations connected to it. Some interviews were also conducted with social actors who act in the organization of the Forum. We discuss, first, the concepts of migrant transnationalism and universal citizenship, and then contextualize the proposition of WSFM and analyze aspects of communication related to the uses of internet made by migratory movements in the construction of universal citizenship agenda, from the experience of WSFM.